EFEITOS HEMODINÂMICOS E PADRÕES AUTONÔMICOS EM ESTUDANTES COM PRESSÃO ALTERADA: IMPACTOS DA APTIDÃO CARDIORRESPIRATÓRIA, CRONONUTRIÇÃO E HÁBITOS ALIMENTARES - LIMA, Gustavo de Sá Oliveira (2024)
Objective: To evaluate the possible hemodynamic effects after a cardiorespiratory fitness test, as well as autonomic patterns, chronic nutrition and eating habits of students from São João dos Patos-MA. Materials and Methods: This is a cross- sectional study carried out with 44 children and adolescents aged 11 to 14, in volunteers with increased blood pressure (n=22). The experimental group (EG) was compared to the control group (CG) (n=22). The effects of the 6-minute run and walk test on systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR) were analyzed between the moments (rest, immediately after the test, 15 and 30 minutes after the test). A digital BP monitor model HBP-1100 was used to assess blood pressure. Anthropometric measurements (weight (kg) and height (m), using the OMRON HBF-514 C digital scale and ES2060 SANNY stadiometer). In addition, body composition, body mass index (BMI = weight/height2) and fat % were assessed (using the Avanutri scientific adipometer), and heart rate variability (HRV) using the HRVCam software. In addition, the food frequency and chrononutrition questionnaire was used to assess diet and habits in relation to the circadian cycle during the school term and at weekends; all these measurements were taken at rest. After the Shapiro-Wilk normality test, the data was reported as mean and standard deviation or median and interquartile ranges, the unpaired t-test or Mann-Whitney U-test were used to compare the quantitative variables, Pearson's chi-square, One-way independent ANOVA and Two-way ANOVA of repeated measures, Pearson's linear correlation, with a significance level of p<0.05. Results: There was a reduction in SBP after 30 minutes of activity among the SG (118.3±10.5 vs 109.2±11.3 mmHg). For the CG, it remained the same after 30 minutes (112.2±11.6 vs 112.6±14.0) with no statistical difference (p>0.05). For DBP, there was no significant variation (p>0.05) between the groups and between the time points. For HR, there was a significant increase between the SG and CG groups immediately after the test (91.36±11.6 vs 110.9±12.2 and 88.2±17.7 vs 101.7±15.5) bpm. Only BMI and the time and frequency domains SDNN, PNN50 and HF showed a statistical difference between the two groups (p<0.05), with these indices showing higher values in the CG compared to the SG. For the dietary assessment, among the items, food consumption of milk, oils, cereals, sausages, fruit and vegetables, sweets and drinks, there was a statistical difference between the two groups compared to the recommended indices for the age group and gender (p<0.05). There was a statistical difference between the misalignment of nocturnal latency between the two groups (p<0.05). Conclusion: There was a significant clinical reduction in SBP after 30 minutes of running and walking tests in the experimental group, with higher values in the SDNN and PNN50 time domains among the CG. Another noteworthy factor is the uneven consumption between the diet consumed and the recommended diet. And a misalignment of nocturnal latency, with lower values for the experimental group, indicating feeding close to bedtime. Further research is therefore needed to elucidate this issue.